2021
DOI: 10.1155/2021/5533416
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Sleep Disorders in Patients on Dialysis: A Cross-Sectional Study in Qatar

Abstract: Patients with end-stage renal disease treated with dialysis have poor quality of life (QOL). Improving QOL in these patients with multiple comorbidities is a large challenge. We performed a cross-sectional study to evaluate the prevalence and associated factors of depression and sleep disorders in this population. Our primary aim was to evaluate QOL measures in dialysis patients in Qatar through a series of validated questionnaires mainly concerning depression and sleep disorders. Our secondary aim was to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
(35 reference statements)
0
8
2
Order By: Relevance
“…The results of the present study showed that the prevalence of poor sleepers in patients undergoing HD was remarkably lower than in previous reports, ranging from 71 to 83.8% in other studies ( 15 18 ). Approximately 30% of patients reported insomnia, from which 21% had clinically significant insomnia.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The results of the present study showed that the prevalence of poor sleepers in patients undergoing HD was remarkably lower than in previous reports, ranging from 71 to 83.8% in other studies ( 15 18 ). Approximately 30% of patients reported insomnia, from which 21% had clinically significant insomnia.…”
Section: Discussioncontrasting
confidence: 85%
“…Each item is rated on a 5-point Likert scale (0 = no difficulty, 4 = very severe problem), which results in a total score that ranges from 0 to 28. The following categories of insomnia are used to interpret the overall score: no insomnia (0-7), sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). There are three versions available: patient, clinician, and significant other.…”
Section: The Insomnia Severity Index (Isi)mentioning
confidence: 99%
“…Corona radiata includes the ascending and descending fibers of the thalamus and cerebral cortex and participates in various functions such as emotion, execution, and cognition (Drevets et al, 2008;Cui et al, 2020). Studies have confirmed that the incidence of depressive symptoms in patients with CKD is significantly higher than that of ordinary people (Fischer et al, 2012;Al-Ali et al, 2021). Therefore, we suspect that the WM damage of CR may be related to a certain degree of depressive symptoms in the enrolled patients.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding gender associations, we have found that female patients had a significantly higher depression score than male patients, a finding supported by other studies. 17 , 18 , 20 , 23 , 31 , 32 To our knowledge, only one study showed higher male depression scores. 25 Some studies failed to show any differences between males and females in that regard.…”
Section: Discussionmentioning
confidence: 71%